First occurrence of the Indo-Pacific polychaete species Glycinde bonhourei Gravier, 1904 in the Hellenic seas (Northern Evvoikos Gulf) - SIMBOURA, N. (Mediterranean Marine Science, 2008)
A specimen of Glycinde bonhourei Gravier, 1904, an Indo-Pacific species, was found at a station near the metalliferous waste disposal in the Northern Evvoikos Gulf (Aegean Sea, eastern Mediterranean). This is the second report of this species in the Mediterranean Sea after its first finding in the Levantine basin (Israel and Egypt). This paper provides new information on its distributional range in the Mediterranean Sea.